.Jamu Potential as Tourism Attraction of Sukoharjo, Central Java – A Review - Hendri Gigih Saputro; Annisa Noor Rachmawati; Putra Pratomo Hadi (Yayasan Literasi Sains Indonesia, 2025)
Sukoharjo Regency holds considerable potential to be developed as a jamu-based tourism destination by utilizing its cultural heritage and the community's expertise in traditional herbal medicine. This study finds that the integration of cultural preservation, product innovation, and digital promotion is crucial in strengthening the identity of Sukoharjo as the